The Therapeutic Potential of Quercetin in Parkinson's Disease: Insights into its Molecular and Cellular Regulation - Tamtaji, Omid Reza; Hadinezhad, Tooba; Fallah, Maryam; Shahmirzadi, Arash Rezaei; Taghizadeh, Mohsen; Behnam, Mohammad; Asemi, Zatollah (Current drug targets, 2020)
Parkinson's disease (PD) is a chronic and progressive neurodegenerative disorder characterized by the progressive death of dopaminergic neurons in the substantia nigra pars compacta (SNc). PD is a multifactorial disorder, with several different factors being suggested to play a synergistic pathophysiological role, including oxidative stress, autophagy, underlying pro-inflammatory events and neurotransmitters abnormalities. Overall, PD can be viewed as the product of a complex interaction of environmental factors acting on a given genetic background. The importance of this subject has gained more attention to discover novel therapies to prevent as well as treat PD. According to previous research, drugs used to treat PD have indicated significant limitations. Therefore, the role of flavonoids has been extensively studied in PD treatment. Quercetin, a plant flavonol from the flavonoid group, has been considered as a supplemental therapy for PD. Quercetin has pharmacological functions in PD by controlling different molecular pathways. Although few studies intended to evaluate the basis for the use of quercetin in the context of PD have been conducted so far, at present, there is very little evidence available addressing the underlying mechanisms of action. Various principal aspects of these treatment procedures remain unknown. Here, currently existing knowledge supporting the use of quercetin for the clinical management of PD has been reviewed.